The Role of Media in the Agricultural and Rural Development of ACP Countries. Synthesis Report - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2009)
Twelve-page Executive Summary of the deliberations and papers that took place at CTA's 2009 Annual Seminar on the Role of the Media in Agricultural and Rural Development in ACP Countries.